A study of 1 Peter 3:18- 4:6 : an investigation into the historical background of the doctrine of Christ’s descent into Hades - Stander, Hennie (Hendrik Frederik), 1953- (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2008.